Rohu 2023 G4 families - Hamilton, Matthew; Akhter, Md; Roy, Aashish Kumar; Sarkar, Uzzal Kumar; Kundu, Ramprosad; Rahman, Md. Mustafizur; Shanta, Sirajum Monira; Kamruzzaman, Md.; Hossain, Jamal; Haque, Mojammel; Hossain, Md.; Sarkar, Anutosh; et al. (WorldFish, 2023)
2023 families produced in WorldFish Rohu Genetic Improvement Program